Adolescent maturation of inhibitory inputs onto cingulate cortex neurons is cell-type specific and TrkB dependent - Vandenberg, Angela; Piekarski, David J.; Caporale, Natalia; Munoz-Cuevas, Francisco Javier; Wilbrecht, Linda (Frontiers in Neural Circuits, 2015)
The maturation of inhibitory circuits during adolescence may be tied to the onset of mental health disorders such as schizophrenia. Neurotrophin signaling likely plays a critical role in supporting inhibitory circuit development and is also implicated in psychiatric disease. Within the neocortex, subcircuits may mature at different times and show differential sensitivity to neurotrophin signaling. We measured miniature inhibitory and excitatory postsynaptic currents (mIPSC and mEPSCs) in Layer 5 cell-types in the mouse anterior cingulate across the periadolescent period. We differentiated cell-types mainly by Thy1 YFP transgene expression and also retrobead injection labeling in the contralateral cingulate and ipsilateral pons. We found that YFP- neurons and commissural projecting neurons had lower frequency of mIPSCs than neighboring YFP+ neurons or pons projecting neurons in juvenile mice (P21-25). YFP- neurons and to a lesser extent commissural projecting neurons also showed a significant increase in mIPSC amplitude during the periadolescent period (P21-25 vs. P40-50), which was not seen in YFP+ neurons or pons projecting neurons. Systemic disruption of tyrosine kinase receptor B (TrkB) signaling during P23-50 in TrkBF616A mice blocked developmental changes in mIPSC amplitude, without affecting miniature excitatory post synaptic currents (mEPSCs). Our data suggest that the maturation of inhibitory inputs onto layer 5 pyramidal neurons is cell-type specific. These data may inform our understanding of adolescent brain development across species and aid in identifying candidate subcircuits that may show greater vulnerability in mental illness.